Some aspects of teaching combinatorics and statistics - Kavaliauskas, Algis; Žilinskienė, Inga (Lietuvos matematikos rinkinys, 2011)
The paper deals with some definitions of combinatorial and statistical terms. Trying to find out why some certain knowledge of combinatory, probability theory ant statistics is difficult to acquire for pupils, some schoolbooks of mathematics are examined. The definitions of terms like Combinations, Arrangements, Sample are analyzed. Some shortcomings of the definitions are highlighted together with proposals for their improvement.